Pelatihan Pengolahan Tepung Ipomea Batatas Desa Embacang Baru Ilir Kecamatan Karang Jaya - Ivoni Susanti; Fitria Lestari (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Embacang Baru Ilir Village has potential land for yam, also known as purple yam or the Latin name Ipomea batatas, which can be processed into a high-value product, namely flour. Ipomea batatas flour has nutritional content and benefits, such as being useful for diabetes sufferers because it is free of gluten, osteoporosis, prevents high blood pressure and is easy to produce. Apart from that, it is hoped that the processing of Ipomoea batatas flour can increase the productivity of the people of Embacang Baru Ilir village, thereby improving their economy. Methods in activities, namely: observation, socialization, training and continued direct practice in making Ipomea batatas flour, as well as providing assistance in production and business management. The results of the activity showed that there was an increase in community skills through observations in terms of material selection, manufacturing processes and product results, namely from 25% (initial skill value) to 95% (final skill value). It was concluded that this activity was beneficial for the people of Embacang Baru village in processing the abundant local potential in their area into products that have marketable value and are useful in the future